Importance of pulmonary imaging diagnostics in the management of febrile neutropenic patients - Heußel, Claus Peter (Mycoses, 2011)
Early detection and characterisation of a pulmonary focus is a major goal in febrile neutropenic patients. Thus, an intensive interdisciplinary co-operation between radiologists and haemato-oncologists on a patient basis, as well as on a department basis is essential to develop a differential diagnosis. The radiologist can contribute much to a differential diagnosis if information about the patient’s disease, status and medication is made available. On the other hand, the haemato-oncologist needs to understand the opportunities and limitations of imaging techniques to evaluate better the images and results. This article focuses on pneumonia as the most common focus. First, imaging techniques are summarised shortly. Then, the perspectives for imaging techniques beyond early detection of pulmonary foci - exclusion of pneumonia, monitoring, characterisation of infiltrates and guidance for intervention - are reviewed.
First published: 03 December 2010
Gesehen am 21.09.2022